Pediatric outdoor recreational injuries: another hidden concern during the COVID-19 pandemic - Melissa P. Blumberg; Michael A. Gittelman; Wendy J. Pomerantz (BMC, 2023)
Abstract Background Recreational equipment sales rose significantly during the COVID-19 pandemic. This study investigated changes in the incidence of pediatric emergency department (PED) visits related to outdoor recreational activities during the COVID-19 pandemic. Methods A retrospective cohort study was conducted at a large children's hospital with a level 1 trauma center. Data were obtained from PED electronic medical records of children 5-14 years with a visit from March 23-September 1 in years 2015-2020. Patients with an ICD-10 code for injury associated with recreation and use of common outdoor recreational equipment were included. Initial pandemic year, 2020, was compared with pre-pandemic years (2015-2019). Data collected included patient demographics, injury characteristics, deprivation index, and disposition. Descriptive statistics were used to characterize the population and Chi-squared analysis was used determine relationships between groups. Results There were 29,044 total injury visits during the study months with 4715 visits (16.2%) due to recreational mechanisms. A higher proportion of visits due to recreational injury visits occurred during the COVID pandemic (8.2%) compared to before (4.9%). Comparing patients included within the two times, were no differences in sex, ethnicity, or ED disposition. During the COVID pandemic, there was a higher percentage of White patients (80% vs 76%) and patients with commercial insurance (64% vs 55%). There was a significantly lower deprivation index for patients injured during the COVID pandemic. There were more injuries due to bicycles, ATV/motorbike, and non-motorized wheeled vehicles during the COVID pandemic. Conclusions During the COVID-19 pandemic, there was an increase in bicycle, ATV/motorbike, and non-motorized wheeled vehicle injuries. White patients with commercial insurance were more likely to be injured compared to years prior. A targeted approach to injury prevention initiatives should be considered.